STRATEGI DESAIN PASIF UNTUK MENCAPAI KENYAMANAN TERMAL MELALUI BUKAAN DAN ELEMEN PENEDUH PADA FASAD BANGUNAN - Cynthia Permata Dewi (Universitas Islam Malang, 2023)
Elevated temperatures are often resulting a problem of thermal comfort in hot humid climates, especially in urban areas that have high building densities. The lack of variety of window opening elements in utilizing natural ventilation often occurs in residential areas. This study aims to determine the combination of window opening elements and shading elements that can increase airspeed. This experimental research used CFD computer software to help simulate airflow. The results of this study found that the best combination is the use of sliding windows with 0.5m shading elements attached to the façade. However, the increase in airspeed in the room still does not meet the minimum speed standards based on the microclimate requirements. Keywords: Simulation; Facade; Openings; Shading; Airspeed.